GOOD JUDGMENT AND PUBLIC ACCOUNTING PRACTICE. - Campfield, William L. (The Accounting Review, 1952)
Abstract It is a commonplace of modem industrial living that accounting methodology may be applied to the economic aspects of any group of transactions which are important enough to be evaluated, classified, and summarized as the basis for guidance of some person or persons. While it is true that the economic aspects of living are not the only important phase of human effort and activity they are, nevertheless, present in practically all activities involving the provisions of goods and services, Hence, accounting technique is not something completely separate from the facts of every day existence. Broadly conceived, every entry made according to accounting methodology is the result of a human judgment based, primarily, on an attempt to arrange a heterogeneous mass of economic data item by item according to a logically consistent scheme. This judgment in the first instance centers around an administrative determination of whether a transaction or transactions should be undertaken and in the second instance on a refitting of the money facts regarding the transactions into the accounting pattern of the business entity concerned.